Reaktualisasi Filsafat Sebagai Landasan Nilai Budaya Dalam Menghadapi Transformasi Digital Masyarakat Indonesia - Faishal, Muhammad (Jayapangus Press, 2025)
The rapid digital transformation has affected various aspects of Indonesian society, including the shifting cultural value system. In the midst of these changes, philosophy has an important role as a foundation for critical and reflective thinking in responding to social impacts and cultural changes due to digitalization. This research aims to review the relevance of philosophy as a basis for formulating and maintaining cultural values that are appropriate to the context of the digital era. The method used is a descriptive qualitative approach with literature study techniques that examine various literature related to philosophy, culture, and digital transformation. The results showed that philosophy can be re-actualized as a normative guide in facing the challenges of the times, such as cultural identity crisis, ethical degradation, and social alienation that often appear in the digital space. Philosophy helps people develop critical thinking, reflective awareness, and a deeper value orientation in interpreting change. It also serves as a means to integrate local values with global developments, thus creating an adaptive cultural foundation that remains rooted in national identity. The conclusion of this research is that the reactualization of philosophy is a strategic step in maintaining the sustainability of Indonesian cultural values in the midst of rapid digitalization. Philosophy is not only a theoretical framework, but also a practical force in forming a strong and sustainable cultural awareness.